2017
DOI: 10.1515/auseb-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive Work Behaviors: a Socio-Demographic Characteristic-Based Study among Employees in the Nigerian Maritime Sector

Abstract: Abstract. The prevalence of counterproductive work behavior (CWB) does not only differ across industries but also varies signifi cantly according to sociodemographic characteristics. This study examines CWB and socio-demographic characteristics among selected employees in the Nigerian maritime industry. Causal research design was adopted to survey 1,000 employees selected through multistage sampling approach in three selected parastatals (Nigerian Ports Authority, Nigerian Maritime Administration and Safety Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
8
2
1
Order By: Relevance
“…Perilaku kontraproduktif yang dimaksud antara lain keluar tanpa izin pada saat jam kerja, bolos, memperpanjang waktu istirahat, pulang kerja lebih dulu sebelum waktunya, bergosip, menggunakan fasilitas kantor di luar kepentingan pekerjaan, mengakses internet untuk hal yang tidak ada kaitannya dengan pekerjaan, bullying, korupsi, dan lain sebagainya (Suyasa, 2015). Perilaku kerja kontraproduktif merupakan masalah utama di tempat kerja yang memiliki kecenderungan mengganggu dan membahayakan organisasi (Uche, George & Abiola, 2017). Perilaku kerja kontraproduktif berpotensi untuk dilakukan oleh karyawan dari berbagai jenis profesi (Nurfianti & Handoyo, 2013).…”
Section: Pendahuluanunclassified
“…Perilaku kontraproduktif yang dimaksud antara lain keluar tanpa izin pada saat jam kerja, bolos, memperpanjang waktu istirahat, pulang kerja lebih dulu sebelum waktunya, bergosip, menggunakan fasilitas kantor di luar kepentingan pekerjaan, mengakses internet untuk hal yang tidak ada kaitannya dengan pekerjaan, bullying, korupsi, dan lain sebagainya (Suyasa, 2015). Perilaku kerja kontraproduktif merupakan masalah utama di tempat kerja yang memiliki kecenderungan mengganggu dan membahayakan organisasi (Uche, George & Abiola, 2017). Perilaku kerja kontraproduktif berpotensi untuk dilakukan oleh karyawan dari berbagai jenis profesi (Nurfianti & Handoyo, 2013).…”
Section: Pendahuluanunclassified
“…The choice of control variables was based on theoretical perspectives and/or empirical findings. A study by [82] reported that CWB varies significantly across social demographic characteristics. With regard to age; metaanalyses confirmed that age consistently correlates negatively with CWB, regardless of category [8].…”
Section: Covariatesmentioning
confidence: 99%
“…As early as possible managerial parties must be able to limit the opportunities for CWB to emerge in the work environment [5]. A thorough understanding of the employee's personality is one important step towards understanding and at the same time, a better approach to improving the impact of CWB in the workplace [44].…”
Section: Problem Statementmentioning
confidence: 99%